(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The conversations about fiscal federalism,decentralization and devolution have been evolving in the literature since thesecond half of the 20th century. In the United States and all around the world,the matter of governance and decentralization are on the agenda. This paperaims to find the routes of fiscal federalism by first understanding what ismeant by federalism, as it does not simply refer to a form of governance, thenlaying out the classical foundations of this theory (trumped by WallaceOates), and followed by some departures from the classical thoughts into some new streams of literature on the matter.